THE IMPORTANCE OF STATE UNITS IN FORMING QUALITY PRESS SERVICE ACTIVITY IN UZBEKISTAN (Multidisciplinary Journal of Science and Technology, 2024)
In society openness policy good quality and impressive way organize reach in processes the press service state units and their place about